(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The Authors report the first record in ltaly of the Eulophidae Pediobius bruchicida (Rondani) as hyperparasitoid of Ooencyrtus pityocampae (Mercet), primary egg-parasitoid of the Pine Processionary Caterpillar. lnforrnations are given about biology, taxonomy of the species with brief morphological data and the originai drawing.